ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s, 1990)
President Samuel Kanyon Doe's talk on Independence Day 1990; rebel incursion in Montserrado; 1990 sports meet update.
Keywords: News; Public Affairs